Heat-resistant aluminum cast iron for cast parts of thermal units - A. V. Shestakov; D. A. Volkov; V. L. Rassudov; V. A. Lisovsky; A. D. Volkov; A. S. Glamazdin (Литьë и металлургия, 2000)
Given are the results of research of technological elements of production of technological elements of production of heat- resistant cast iron with high Al content as a substitute for the high chromium type 4X28 cast iron.